Mediterranean forested wetlands are yeast hotspots for bioremediation: a case study using azo dyes. Issue 1 (December 2018) - Sampaio, Ana; Bezerra, Rui; Dias, Albino
Abstract Forested wetlands are interfaces between terrestrial and aquatic environments. These ecosystems play an important role in the hydrology, chemistry and biodiversity maintenance. Despite their high microbial diversity, there has been a lack of attention to the potential of their yeast communities. The purpose of this study is to evaluate the potential of yeasts isolated from a Mediterranean forested wetlands in decolorizing azo dyes. Azo dyes are synthetic, and highly recalcitrant to degradation. Ninety-two out of 560 isolates were randomly chosen to assess their ability to decolorize five azo dyes. Hierarchical clustering based on medium color changes during incubations was used to evaluate the isolates' decolorization performance. All of the isolates that best degraded the 5 dyes tested were identified as Basidiomycota (Filobasidiales, Tremellales and Sporidiobolales). This work identifies new azo dye-degrading yeast species, and supports the hypothesis that forested wetlands are a niche for yeasts with bioremediation potential - namely azo dyes removal.